Instability Mechanism of Cavity-Bearing Formation under Tunnel Excavation Disturbance - Tao Liu; Haotong Wang; Xiuting Su; Kexian Li; Shiqun Liu; Fengsong Guo (Advances in Civil Engineering)
Urban subway construction inevitably causes disturbances to the rock strata. It can even cause ground collapse accidents when construction encounters a bad geological body in the stratum. To verify the influence of cavities on surface settlement and the mechanism of formation instability, the instability mechanism of cavity-bearing strata under tunnel excavation disturbance was herein studied by tests using self-designed indoor models and numerical simulations. This study was based on the concrete project case of Qingdao Metro. Two groups of experiments (with and without cavities) were designed to simulate the four-step excavation by staged unloading of an airbag. The results show that the settlement value in the cavity state was about twice as much as that in the nonvoid state at the same stage. Besides the first step of excavation, in the numerical simulation, the settlement value of the same stage is about 1.3 times that of the model test. Simulating the deformation process of the surrounding rock in model tests shows that, in the excavation of the tunnel, the collapse surface of the tunnel arch roof will be connected with the sliding surface of the formation cavity. The cavity will gradually change from a regular circle to an ellipse or may even close, resulting in a sudden increase in land subsidence or even ground collapse. This indicates that disturbance during tunnel excavation would cause greater instability in a stratum when bad geological bodies, such as cavities, exist in the stratum.